Limiting membrane and diffusion behavior of a compacted sand-bentonite mixture for hydraulic and chemical containment - Fritz, Cameron John, author; Scalia, Joseph, IV, advisor; Shackelford, Charles D., advisor; Ronayne, Michael J., committee member (Colorado State University. Libraries, 2017)
Sodium-bentonite (Na-bentonite) commonly is used either as an additive component or as the sole component of engineered barriers used for waste containment applications, because the tendency of Na-bentonite to exhibit high swell can result in the restriction of advective and diffusive contaminant transport. Additionally, compacted mixtures of Na-bentonite and sand can be an effective and economical alternative to barrier materials consisting only of natural clay (e.g., compacted clay liners) if the use of natural clay is not logistically or economically feasible. The existence of membrane behavior, i.e., the ability of a porous material to exhibit selective restriction of migrating chemical species from the clay pores, previously has been shown for typical engineered bentonite-based barriers commonly used in hydraulic and chemical containment applications, including compacted sand-bentonite (SB) mixtures. However, the extent to which clay membrane behavior may persist in the presence of highly concentrated chemical solutions, which have been shown to have an adverse effect on the magnitude of membrane behavior in clays, remains largely unknown, with few studies having quantified the limiting membrane and diffusion behavior of bentonite-based barrier materials. Moreover, the limiting membrane and diffusion behavior of compacted SB mixtures has not yet been evaluated. Based on these considerations, the purpose of this study was to quantify the limiting membrane and diffusion behavior of two specimens of a compacted SB mixture comprising 15 % Na-bentonite (by dry weight) by determining the threshold salt concentration at which measurable membrane behavior was eliminated. The specimens were exposed to a series of boundary monovalent salt solutions with increasingly higher source concentrations, Cot, until measured values of the membrane efficiency coefficient, ω (0 ≤ ω ≤ 1), were effectively nil (i.e., 0.000), representing the limiting condition at which measurable membrane behavior was eliminated. Overall, ω decreased from an average of 0.032 to 0.000 as Cot increased from 160 mM KCl to 3.27 M NaCl, resulting in a threshold concentration between 1.63 M and 3.27 M NaCl for both specimens that was much higher than the range of salt concentrations for which measurable membrane behavior previously was thought to exist. Effective diffusion coefficients, D*, for nonreactive chloride (Cl-) also were measured during membrane testing to evaluate possible changes in diffusion behavior corresponding to the progressive destruction of membrane behavior. However, D* was relatively constant throughout all testing stages (2.1 x 10-10 m2/s ≤ D* ≤ 3.0 x 10-10 m2/s), indicating that the corresponding decrease in ω from 0.032 to 0.000 had little to no effect on the diffusion of Cl-.
Keywords: bentonite; sand-bentonite; van't Hoff; diffusion; activity method; semipermeable membrane